Presentation of case: Bladder cancer in an 18 year old female patient. (2015) - Sheehan, Lisa; Anwar, Adeel; Kommu, Sashi
Abstract: Introduction: Bladder cancers are not very common in the young population below 20 years of age, especially in those who have not been exposed to chemotherapy, bladder augmentation surgery and other known risk factors. By highlighting this case we hope to raise awareness in the medical community, that the symptom of visible haematuria can potentially be due to a bladder malignancy and therefore this should be thoroughly investigated. Presentation of case: An 18-year-old female presented with intermittent macroscopic haematuria and non-specific abdominal pain. Physical examination and routine blood tests were normal. An ultrasound scan initially showed a bladder wall lesion, which a flexible cystoscopy confirmed. Histology revealed grade 2 papillary transitional cell carcinoma of the bladder with no invasion into the lamina propria (G2pTa TCCB). Discussion: We recognise through our literature review that paediatric bladder cancers are not commonly reported in the UK. In our paper we highlight the relevant major studies that have been carried out world-wide, the reported incidence so far and gaps in the evidence base. Conclusion: Despite the dearth of data about paediatric bladder malignancies there is enough case-based evidence, from world-wide sources, to support that bladder cancer must be suspected in the event of macroscopic haematuria. Ultrasound and cystoscopy are the standard diagnostic tools for bladder tumours. Endoscopic resection of the tumour followed up by interval ultrasound scans and flexible cystoscopy checks remain the mainstay of treatment hitherto.